Could It Be Post Transplantation Lymphoproliferative Disorder at this period in a Live Donor Kidney Transplant Recipient - Matter, Yasser Elsayed; Abbas, Mohamed Hamed; Khater, Sheiri; Elhadedy, Muhammed Ahmed; Megahed, Ahmed Samir; MD, Hussein Atia Shaeashaa (International Journal For Research In Health Sciences And Nursing, 2016)
Objectives: Post-Transplantation Lymphoproliferative Disorder (PTLD) is a wellrecognized complication of renal transplantation. The typical histopathological changes of PTLD could be a large increase in the number of B cell lymphocytes in lymphoid tissues, accompanied by multiple focal areas of necrosis. Plasma cell-rich acute rejection (PCAR) is a relatively new clinical entity and is characterized by the presence of mature plasma cells that comprise more than 10% of the inflammatory cells infiltrating a renal graft. PCAR shows findings similar to those of posttransplantation lymphoproliferative disorder (PTLD).So we should differentiate between PTLD and PCAR for appropriate treatment. Case Report: We report a 32-year-old male underwent living donor kidney transplantation from his 40- year sister at March, 2014. Unfortunately, at 8th day post transplantation his serum creatinine increased suddenly to 1.8 mg/dl with good urine output and unremarkable physical examination. Graft Ultrasound and Doppler showed no back pressure, perfect perfusion, so graft biopsy was carried out with starting empirical pulse steroid and plasma exchange. Graft biopsy revealed picture of Lymphoproliferative disorder which is uncommon picture at this early post-transplantation. Conclusion: PCAR shows findings similar to those of PTLD and has a poor response to standard antirejection therapy and worse graft outcome. Hence, early diagnosis and management of this morphology in a renal allograft biopsy is essential for appropriate patient and graft survival.